(untitled) (Journal of Enam Medical College, 2014)
Chronic kidney disease (CKD) is a worldwide public health problem with an increasing incidence and prevalence. Outcomes of CKD include not only complications of decreased kidney function and cardiovascular disease but also kidney failure causing increased morbidity and mortality. Unfortunately, CKD is often undetected and undertreated because of its insidious onset, variable progression, and length of time to overt kidney failure. Diabetes is now the leading cause of CKD requiring renal replacement therapy in many parts of the world, and its prevalence is increasing disproportionately in the developing countries. This review article outlines the current recommendations from various clinical guidelines and research studies for treatment, prevention and delaying the progression of both CKD and its common complications such as hypertension, anemia, renal osteodystrophy, electrolyte and acid-base imbalance, and hyperlipidemia. Recommendations for nutrition in CKD and measures adopted for early diabetic kidney disease to prevent further progression have also been reviewed. There is strong evidence that early detection and management of CKD can prevent or reduce disease progression, decrease complications and improve outcomes. Evidence supports that achieving optimal glucose control, blood pressure, reduction in albuminuria with a multifactorial intervention slows the progression of CKD. Angiotensin-converting enzyme inhibitors and angiotensin-II receptor antagonists are most effective because of their unique ability to decrease proteinuria, a factor important for the progression of CKD. DOI: http://dx.doi.org/10.3329/jemc.v4i1.18069 J Enam Med Col 2014; 4(1): 45-55